"In Praise of Wool": The development of partition chromatography and its under-appreciated impact on molecular biology. Issue 4 (December 2019) - Hall, Kersten
Highlights: This article explores how research into wool played a crucial, but little known, role in the rise of molecular biology. Novel archival sources show how A.J.P. Martin & R.L.M. Synge's studies of wool, were crucial for later work on proteins & DNA. New sources show Martin & Synge knew that their technique could be used to determine the sequence of amino acids in a protein. Abstract: The invention of partition chromatography by the biochemists Archer Martin and Richard Synge in 1941 offered crucial insights into the structure and function of DNA, insights at least as important as those from X-ray crystallography. Even so, the role that partition chromatography played in molecular biological studies is far less well known. Using new archival material, this article describes the origins of Martin and Synge's work, arguing that their achievement was far more than a new technical innovation; it went on to have a profound impact on the development of molecular biology to an extent that scholars have insufficiently appreciated.